Purification mechanism of city tail water by constructed wetland substrate with NaOH-modified corn straw biochar - Hanxi Wang; Xinyu Wang; Haowen Teng; Jianling Xu; Lianxi Sheng (Ecotoxicology and Environmental Safety, 2022)
The pollution of corn straw to the environment had attracted much attention. The preparation and alkali modification of corn straw biochar as the constructed wetland (CW) substrate was conducive to solving the environment pollution caused by straw and improving the purification effect of CW. The NaOH modification mechanism of corn straw biochar was analyzed by measuring the surface morphology, element content, specific surface area (SSA), pore volume, crystal structure, surface functional groups and CO2 adsorption. Biochar prepared under relatively optimal NaOH-modified conditions was used as the vertical flow CW substrate to treat city tail water. The results showed that controlling the modification condition of NaOH (< 1.0 mol·L−1, ≤ 24 h) was conducive to prevent the biochar structure destruction and C element reduction. The SSA and pore volume of NaOH (0.1 mol·L−1) modified biochar are 360 m2·g−1 and 0.109 cm3·g−1, respectively. The biochar adsorption for CO2 conformed to the Langmuir and Freundlich isothermal adsorption theoretical model (R2 > 0.9). The maximum adsorption capacity of CO2 by modified biochar with NaOH (0.1 mol·L−1) was 64.516 cm3·g−1 and increased by 10.3%. The city tail water treated by CW with plants showed that the removal rates of ammonia nitrogen, total nitrogen and nitrate nitrogen reached about 90%. The research results improved the utilization value of straw, realized straw carbon sequestration and promoted the progress of CW technology.